Intergeneric chromosome-specific painting reveals differential chromosomal transmission from Tripidium arundinaceum in sugarcane progeny - Fan Yu; Zehuai Yu; Jin Chai; Xikai Yu; Chen Fu; Xinwang Zhao; Hailong Chang; Jiawei Lei; Baoshan Chen; Wei Yao; Muqing Zhang; Jiayun Wu; et al. (Journal of Integrative Agriculture, 2024)
Sugarcane has recently attracted increasing attention for its potential as a source of sugar and bioethanol, so increasing its yield is essential to ensure the sugar security and bioenergy production. Intergeneric hybridization is a highly efficient method to produce new genetic variants of crop plants, particularly those species with high ploidy such as sugarcane (Saccharum spp.). Tripidium arundinaceum exhibits many desirable agronomic traits, and has been widely studied to produce hybrids with improved stress tolerance and other characteristics in sugarcane breeding. However, the genetic relationship between T. arundinaceum and Saccharum species, and the individual T. arundinaceum chromosomal compositions in sugarcane hybrids are still elusive. Here we used whole-genome single-nucleotide polymorphisms (SNPs) to ascertain the phylogenetic relationships between these species and found that T. arundinaceum is more closely related to Saccharum than Sorghum, in contrast to the previous narrow genetic analyses using chloroplast DNA. Additionally, oligonucleotide (oligo)-based chromosome-specific painting derived from Saccharum officinarum was able to distinctly identify the chromosomes of T. arundinaceum. We developed the oligo-genomic in situ hybridization (GISH) system for the first time, to unveil the novel chromosome translocations and the transmission of individual T. arundinaceum chromosomes in sugarcane progeny. Notably, we discovered that the chromosomal transmission of T. arundinaceum exhibited several different inheritance modes, including n, 2n, and over 2n in the BC1 progenies. Such inheritance patterns may have resulted from first division restitution (FDR) or FDR+nondisjunction of a chromosome with the sister chromatids in the second meiosis division/second division restitution (FDR+NSC/SDR) model during meiosis. These results will be of substantial benefit for the further selection of T. arundinaceum chromosomes for sugarcane genetic improvement.